PENGARUH METODE RGEC TERHADAP NILAI PERUSAHAAN PADA BANK KONVENSIONAL YANG TERDAFTAR DI BEI - Rahandhika Ivan Adyaksana; Vidya Vitta Adhivinna; M.Sulkhanul Umam; Fitria Nuri Agustin (UNIB Press, 2024)
The purpose of this study is to determine how the influence of RGEC indirectly or not on company value. This research was conducted on conventional banking companies listed on the Indonesia Stock Exchange (IDX) in the period 2017 – 2021. This research uses quantitative methods by obtaining 38 conventional banking companies using this data analysis technique using smartPLS. From the results of the study shows that risk profile has a significant negative influence on company value, GCG (Good Corporate Governance) has a significant positive influence on company value, Earning has a significant positive influence on company value, and Capital has a significant positive influence on company value. The company’s own value uses PBV (Price Book Value).